Pure brucellar discitis mimicking lumbar disc herniation: A case report and review of the literature [Lomber disk hernisini taklit eden saf brusellar diskit: Bir olgu sunumu ve literatürün gözden geçirilmesi] - (:unkn) unknown (My University, 2013)
Brucellosis is a zoonotic infection, endemic in the Middle East, the Mediterranean region, Central and South America. Osteoarticular involvement is the most common form of the disease process with spinal complications in third place in this group. We presented a 36-yearold male patient with signs and symptoms of lumbar disc herniation. On lumbar magnetic resonance imaging, a right-sided L5-S1 disc extrusion was detected and the patient was operated. Frozen material pointed out an inflammatory process with Brucella melitensis in disc specimen culture. He was put on rifampicin and doxycycline chemotherapies. After 6 months of follow-up; his clinical, laboratory, and radiological findings became normal. Medical treatment was stopped with ongoing routine outpatient follow-ups. Discitis without spondylitis in Brucella infection is very rare. There have been 2 case reports in the literature. Also, Brucella disc infection should be in differential diagnosis of lumbar disc herniation clinic in endemic parts of the world.
Keywords: Brucellar discitis; Lumbar disc herniation; MRI; Spine